Impact of exogenous application of Indole Acetic Acid on accumulation of heavy metal and antioxidants in wheat (Triticum aestivum L.) under sewage water irrigation - Kumar, Chandra Shekhar; Singh, Alka; Sagar, R K; Negi, M.P.S; Maurya, J N (Recent Research in Science and Technology, 2012)
A field experiment was conducted to study the activities of antioxidative enzymes SOD, CAT & GR, non-enzymatic antioxidants i.e. carotenoid & proline and uptake of heavy metals (Pb, Cr, Zn, Cu and Fe) in winter wheat (Triticum aestivum L.) variety PBW-343 grown under sewage water (SW) collected from Quilla channel of Bareilly city (U.P), India. Wheat was irrigated with two concentrations (50% and 100%) of sewage water along with exogenous application of 10 and 20 ppm Indole-3 Acetic Acid (IAA). Enzymatic and non-enzymatic antioxidant was significantly higher in 100% SW as compared to 50% SW. There was a significant (p<0.001) increase in carotenoid and proline content whereas decrease in uptake of toxic heavy metals was observed in wheat irrigated with SW+10 and 20 ppm IAA as compared to SW and control. Further, significant (p<0.001) decline in carotenoid and proline content was evident in 20 ppm IAA as compared to 10 ppm IAA in both the concentrations of SW. In contrast, under both the concentrations of SW, heavy metals especially Cr found to decrease (p<0.05) whereas significant decrease was also noticed in Zn, Cu and Fe uptake on application of 20 ppm IAA as compared to 10 ppm IAA and SW alone. <!--[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif][if gte mso 9]>